3n + 10 chia hết cho n - 1
3n - 3+ 13 chia hết cho n - 1
13 chia hết cho n - 1
n - 1 thuộc U(13) = {-13 ; -1 ; 1 ; 13}
n - 1 = -13 => n = -12
n - 1= -1 => n = 0
n - 1 = 1 => n = 2
n - 1 = 13 => n = 14
Vậy n thuộc {-12 ; 0 ; 2 ; 14}
3n+10 chia het cho n-1
=>3.(n-1)+13 chia het cho n-1
=>13 chia het cho n-1
=>n-1 E Ư(13)={1;13}
=>n E {2;15}
3n + 10 chia hết cho n - 1
3n - 3+ 13 chia hết cho n - 1
13 chia hết cho n - 1
n - 1 thuộc U(13) = {-13 ; -1 ; 1 ; 13}
n - 1 = -13 => n = -12
n - 1= -1 => n = 0
n - 1 = 1 => n = 2
n - 1 = 13 => n = 14
Vậy n thuộc {-12 ; 0 ; 2 ; 14}
( tick nha)